Walenty Barczewski's arguments for the Polishness of southern Warmia in the second half of the 19th century (based on the work "Kiermasy w Warmii") - Biolik, Maria (Papers in Linguistics, 2019)
The article presents Priest Walenty Barczewski’s arguments for the Polishness of southern Warmia, which belonged to the Prussian partition in the second half of the 19th century. At that time Warmia saw intensifying nationalistic anatagonisms and at the same time the sense of separateness of Warmians from the Catholic German and Masurian population began to develop. The rise of the national consciousness and the conviction about Warmia’s historical and cultural connection with Poland and the Polish nation was embraced by Priest W. Barczewski, which found confirmation in his work "Kiermasy na Warmii." For Walenty Barczewski Polishness was linked to belonging to "the ancient Polish population" and the attachment of the people to the Catholic religion, which was identified with Polishness. He emphasized the Polishness of Warmia’s dialect, pointed out traditional Polish hospitality and the cultural experiences encoded in the language of Warmia’s inhabitatnts, which were close to the experiences of the Polish people.